The Effect of Corporate Governance Characteristics on Executive Compensation in The Chinese Listed Private Enterprises - Zhang, Yuanjie (2022)
Executive compensation constitutes a significant component in the corporate governance mechanisms. Therefore, the purpose of this paper, which is on the basis of the principle-agency theory and managerial power theory, is to examine the impact of executive power on executive compensation in Chinese listed private enterprises in the manufacturing industry, as measured in both cash compensation (short-term incentive) and equity compensation (long-term incentive). From 2014 to 2019, the research sample consisted of Chinese listed private manufacturing enterprises, employing the fixed effect regression model (two-way). After that, in order to assess the influence of management authority on cash compensation in executive compensation packages, 5855 firm-year observations are collected, whereas 3843 firm-year observations are used to assess the impact of managerial power on equity compensation in executive compensation packages, using STATA to conduct the regression analysis. The study discovers a positive and substantial association between the power of the executive and executive compensation, both measured in cash compensation and equity compensation. Besides, the paper's main contribution is to extend and supplement the literature by considering both the cash component and equity component in the executive compensation package when assessing the effect of managerial power in Chinese listed private firms from the manufacturing industry.